The assessment of the relationship between the vascularity of FIGO Type 4–7 leiomyomas and abnormal uterine bleeding. (2nd January 2022) - Gursoy, Asli Yarci; Cakmak, Didem; Akgul, Gulsah; Kiseli, Mine; Umudum, Haldun; Pabuccu, Recai; Caglar, Gamze Sinem
Abstract: The current study aimed to analyse and compare the vascularity of FIGO Type 4–7 leiomyoma specimens obtained from women with or without abnormal uterine bleeding (AUB). The records of 31 women who underwent myomectomy for FIGO Type 4–7 leiomyomas in a university hospital setting were analysed. Group I ( n = 16) was composed of women that were symptomatic for AUB and group II ( n = 15) consisted of asymptomatic cases. The myomectomy material(s) of each case were processed with CD34 staining and evaluated by Image J ® software (Image J 1.52a, Wayne Rasband National Institutes of Health, Bethesda, MD). There was no statistically significant difference between the rates of vascular areas in the specimens of the two groups ( p >.05). Although areas with large vessels were higher in group I compared to group II, the difference did not reach statistical significance ( p >.05). AUB caused by FIGO Type 4–7 leiomyomas seems to be related to factors other than vascular density. Impact Statement: What is already known on this subject? Uterine leiomyomas are the most common benign gynaecologic neoplasms with a prevalence of approximately 40% in women of reproductive age. They are most often asymptomatic but when symptomatic, abnormal uterine bleeding (AUB) is one of the most commonly observed symptoms. Although there are some hypothetical explanations, the exact pathogenesis underlying leiomyoma-associated AUB has not yet been elucidated. Almost a century ago, the vascular abnormalities of fibroids were hypothesised as one of the etiopathological factors correlated with clinical symptoms, such as AUB, and current data suggest that the vascular map of leiomyomas consists of an avascular core surrounded by a vascularised capsule. To our knowledge, there are no studies in the literature comparing the histopathological evaluation of the vascularity scores of FIGO Type 4–7 leiomyomas in symptomatic (with AUB) and asymptomatic (without AUB) women. What the results of this study add? The study revealed that there was no statistically significant difference between the vascularity scores of FIGO Type 4–7 leiomyomas excised from the symptomatic and asymptomatic women. Large vessel densities also did not statistically significantly differ between the two groups. What the implications are of these findings for clinical practice and/or further research? This study revealed that AUB caused by FIGO Type 4–7 leiomyomas was related to factors other than vascular density.